Community Empowerment to Address Technology and HR Barriers in Rare Earth Development - Felix Sutisna; Ester Ananda Natalia; Dwi Andayani; Umi Rusilowati; Kristina Vaher (ADI Publisher, 2025)
Indonesia holds significant potential in Rare Earth Elements (REE), which play an essential role in supporting the clean energy transition and strengthening national industrialization. However, the downstream development of REE still faces major obstacles in the aspects of technology, infrastructure, and human resources (HR), resulting in suboptimal national value creation. This study aims to describe community empowerment strategies as an alternative approach to overcoming REE downstreaming challenges in Indonesia, emphasizing community involvement in enhancing technological capacity, developing local infrastructure, and improving the quality of human resources. The research employs a qualitative approach based on literature review, descriptive analysis, and reflections from community service practices. Data were obtained from secondary sources such as academic journals, policy reports, and previous studies. The findings indicate that community empowerment can be achieved through local capacity building, collaboration among academics, industry, and communities, as well as infrastructure development tailored to regional needs. This strategy aligns with the Sustainable Development Goals (SDGs), particularly Goal 8 which focuses on decent work and economic growth, Goal 9 which promotes industry, innovation, and infrastructure, and Goal 11 which emphasizes sustainable cities and communities, highlighting inclusive economic development and community resilience. The downstreaming of REE cannot rely solely on top-down industrial policies. Its success requires active community participation through integrated and continuous empowerment strategies to achieve inclusive and sustainable national development.